Batch and Semi-batch Reactors : Practical Guides in Chemical Engineering - Worstell, Jonathan (Waltham, MA ; Oxford, UK : Butterworth-Heinemann, 2015)
Batch and Semi-batch Reactors: Practical Guides in Chemical Engineering is a cluster of short texts that provide a focused introductory view on a single subject. The full library presents a basic understanding of the main topics in the chemical process industries, allowing engineering professionals to quickly access information. Each'pocket publication' can be easily carried or accessed electronically, giving users a highly practical and applied presentation of the first principles engineers need know on a moment's notice. The focused facts provided in each guide help users converse with experts in the field, attempt their own initial troubleshooting, check calculations, and solve rudimentary problems.
Includes bibliographical references.
Vendor-supplied metadata.
Elsevier
Keywords: Chemical reactors; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Chemical reactors; Electronic books